Implementasi Total Quality Manajemen (TQM) Dalam Lembaga Pendidikan Islam - Anis Zohriah; Adnan Adnan; Rijal Firdaos; Muhammad Shofwan Mawally Nafis Badri (Transformasi Manageria: Journal of Islamic Education Management, 2024)
Total Quality Management (TQM) needs to be carried out in educational institutions as a form of efforts to improve the quality of education. This is important for carrying out management functions in every educational institution. This study discusses the implementation of total quality management (TQM) in educational institutions and efforts to improve the quality of education in achieving predetermined quality standards. Every educational institution should show better quality. This is intended so that educational institutions continue to gain the trust of the community and stakeholders. One way to keep getting this is to make continuous improvements, both from physical and non-physical aspects. So that it becomes a quality educational institution and its quality is guaranteed. The implementation of TQM in the world of education provides continuous improvement which refers to the quality standards of educational institutions as the basis for developing quality. Keywords: Total Quality Management (TMQ), Education,